Document Delivery Service by Central Library, Babasaheb Bhimrao Ambedkar University, Lucknow: A Study - Saini, O.P. (DESIDOC Journal of Library & Information Technology, 2014)
Interlibrary loan, also recognised as interloan, interlending, document delivery, or document supply is a service whereby a user of one library can borrow books or receive photocopies of documents that are owned by another library1. Babasaheb Bhimrao Ambedkar University (BBAU), Lucknow is a central university established in 1996. The University became a member of JCCC@UGC–INFONET in April 2008. The present paper discusses theoretical and practical frameworks of document delivery service (DDS) which was initiated by the University in July 2009. The paper deals with the steps and methods involved in DDS. It throws light on the advantages and disadvantages of the service and provides an understanding on the role of INFLIBNET for supporting the service in higher education. For this study, all the available official records were consulted, analysed and presented in tabulated form. The paper highlights the use and utility of the service and gives recommendations for improvement in services. http://dx.doi.org/10.14429/djlit.34.7054